Clinical and diagnostic aspects of non-suicidal self-harming behavior - R. V. Bisaliev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The scientific review is devoted to the actual problem of non-suicidal self-harming behavior. The relevance of this problem is confirmed by the steady increase in cases of various forms of autoaggression in different age categories. Such a high interest in the problem is explained by its high social significance. It is worth noting the insufficient development of the theoretical and methodological base on the phenomenon of non-suicidal self-harming behavior. The aim of the study was theoretical analysis of clinical and diagnostic aspects of non-suicidal self-harming behavior. A theoretical analysis of articles satisfying the criteria requirements has been carried out: the publication presents an analysis of an empirical or experimental study; the study was conducted on persons with suicidal and non-suicidal behavior; the publication is freely available. The analysis of 60 sources of domestic and foreign authors was carried out. The methods of theoretical analysis were used: analytical comparison, systematization and generalization of domestic and foreign works on the problem of non-suicidal self-harming suicidal behavior in a healthy population.The criteria for distinguishing suicidal and non-suicidal behavior are defined. In the process of theoretical analysis, it was established that the criterion of differentiation for the above-mentioned phenomena is the presence / absence of an intention to die, motivation and methods of self-harming acts. The advantages and disadvantages of describing non-suicidal self-harming behavior as an independent clinical phenomenon are revealed. Due to the lack of clear criteria for determining non-suicidal self-harm, the author of this study conducted a theoretical analysis of the problem of non-suicidal self-harming behavior. The analysis of the works confirms the importance of a deeper and more detailed study of the problem of non-suicidal selfharming behavior from the standpoint of research methodology, including issues of diagnosis, classification and differentiated measures for the prevention of autoaggressive behavior.